Turbulent axially directed flow of plasma containing rt-PA promotes thrombolysis of non-occlusive whole blood clots in vitro - Tratar, Gregor; Blinc, Aleš; Štrukelj, Mitja; Mikac, Urša; Serša, Igor (Thrombosis and Haemostasis, 2004)
The rate of thrombolysis markedly decreases after a thrombosed vessel is partly recanalized and the remaining clot poses serious risk for rethrombosis. We studied in vitro how thrombolysis depends on penetration of plasma containing thrombolytic agents – 0.2 μg/ml rt-PA or 250 IU/ml streptokinase (SK) nd the magnetic resonance contrast agent Gd-DTPA (at 1 mmol/l) into non-occlusive clots under conditions of fast (turbulent) or slow (laminar) axially directed flow. Cylindrical non-retracted (fresh) or retracted (aged) whole blood clots were pierced lengthways and connected to a perfusion system. Dynamical spin-echo MRI was used for measuring the penetration of labeled plasma into clots and for assessing the remaining clot size. In both types of clots fast flow enhanced the penetration of Gd-DTPA-labeled plasma into clots in comparison to slow flow. In non-retracted clots, lysis with rt-PA and to a lesser extent also lysis with SK followed the path of plasma penetration into clots. After 40 minutes of fast axially directed flow rt-PA resulted in almost complete lysis and SK left only about a third of the clot undissolved, whereas with slow flow lysis was much slower (undissolved clot: 86 ± 5 % with rt-PA and 95 ± 1 % with SK). In retracted clots, substantial lysis was possible only with rt-PA and rapid flow (53 ± 28% of the clot undissolved after 60 min), whereas the use of SK or slow flow precluded meaningful lysis. We conclude that rapid (turbulent) axially directed flow of plasma along non-occlusive blood clots causes forceful exchange of serum inside the clot with outer plasma which enhances both fibrin-specific and non-fibrin-specific lysis of fresh clots. Dissolution of non-occlusive retracted (aged) clots occurs only under fibrin-specific conditions combined with adequate transport of rt-PA into clots.
Keywords: Flow; turbulent; thrombolysis; blood clots